2021
DOI: 10.3390/cells10051265
|View full text |Cite
|
Sign up to set email alerts
|

Having an Old Friend for Dinner: The Interplay between Apoptotic Cells and Efferocytes

Abstract: Apoptosis, the programmed and intentional death of senescent, damaged, or otherwise superfluous cells, is the natural end-point for most cells within multicellular organisms. Apoptotic cells are not inherently damaging, but if left unattended, they can lyse through secondary necrosis. The resulting release of intracellular contents drives inflammation in the surrounding tissue and can lead to autoimmunity. These negative consequences of secondary necrosis are avoided by efferocytosis—the phagocytic clearance o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 253 publications
(366 reference statements)
0
3
0
Order By: Relevance
“…By addressing the role of TAM receptors, we found that both Axl and Mer promote BMDM-mediated efferocytosis of proapoptotic T cells from T. cruzi-infected mice. Although the sources of macrophages and apoptotic T cells are distinct in this and the previous experimental model, it is conceivable that a few or multiple receptors, such as αvβ3, Axl, Mer, and other putative receptors, such as TIM4 41 , work in concert in efferocytosis, as previously suggested [42][43][44] . Moreover, upon binding to apoptotic cell ligands, receptors might cluster together in an efferocytosisinduced molecular platform dedicated to tethering, phagocytosis, and inhibitory signalling response to apoptotic cells.…”
Section: Discussionmentioning
confidence: 53%
“…By addressing the role of TAM receptors, we found that both Axl and Mer promote BMDM-mediated efferocytosis of proapoptotic T cells from T. cruzi-infected mice. Although the sources of macrophages and apoptotic T cells are distinct in this and the previous experimental model, it is conceivable that a few or multiple receptors, such as αvβ3, Axl, Mer, and other putative receptors, such as TIM4 41 , work in concert in efferocytosis, as previously suggested [42][43][44] . Moreover, upon binding to apoptotic cell ligands, receptors might cluster together in an efferocytosisinduced molecular platform dedicated to tethering, phagocytosis, and inhibitory signalling response to apoptotic cells.…”
Section: Discussionmentioning
confidence: 53%
“…This process of clearing apoptotic cells is called efferocytosis. The efferocytosis process is divided into three stages: recognition, binding, and cell death degradation [ 12 , 13 ]. Various markers of each stage have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the ability of phagocytosis to prevent secondary necrosis of apoptotic cells and the release of autoantigens and proinflammatory alarmins (7). These antiinflammatory effects are particularly important at mucosal locations such as the lung where the epithelium can turn over every 7-21 days (7)(8)(9)(10)(11)(12)(13). Efferocytosis is an evolutionarily conserved, highly regulated, multistep process that includes mononuclear cell recognition of apoptotic cells and the proper interpretation of the signals they send (7).…”
Section: Introductionmentioning
confidence: 99%